The Process of Rapid Eye Movement (REM) Sleep in the Qur'an: Neuroscience Perspective on the QS. Al-Kahfi 18. - Ridhoul Wahidi; Raden Kurnia Kholiska; Afrizal Nur (UIN Sunan Kalijaga Yogyakarta, 2021)
This study aims to understand the scientific concept of sleep in the Qur'an by using data interpretation of QS. Al-Kahfi 18, which is collaborated with neuroscience. The phenomenon of sleep in the story of Ashabul Kahfi is found in QS Al-Kahfi 18. Classical scholars interpreted the verse especially in words aiqazhan wa hum ruqud, meaning that they slept even though many thought they were awake. This interpretation tends to be interpreted as a supernatural phenomenon, whereas in science, such events are paradoxical, which is a phenomenon of open eyes during sleep. This research is qualitative research by utilizing the interpretation of QS. Al-Kahfi 18 and has collaborated with neuroscience. The results of this study showed that the phenomenon of aiqazhan wa hum ruqud in QS Al-Kahfi 18 or between waking and sleeping in neuroscience perspective is a the process of REM (Rapid Eye Movement). Based on a neuroscience the word aiqazhan can be interpreted with the meaning of unsleeping in the phenomenon of rapid eye movement. That is loss of consciousness and control over the body so that it can move unnoticed. It is illustrated in the story of Ashabul Kahfi in QS. Al-Kahfi 18. They fall asleep hundreds of years in the cave, while their eyes open while asleep, and their bodies move to the right and the left. Anyone who sees it will think they are awake, whereas the phenomenon is the body's reaction to the rapid eye movement phase in the sleep cycle.